Cu- and Pd-catalyzed Ullmann reaction on a hexagonal boron nitride layer. Issue 90 (6th October 2016) - Zhao, Wei; Dong, Lei; Huang, Chao; Win, Zaw Myo; Lin, Nian
Abstract : This study demonstrates that Cu and Pd can efficiently activate Ullmann reactions on inert h-BN with two distinctive reaction paths. Abstract : The Ullmann reaction is being widely adopted as a strategy for on-surface organic synthesis. Herein, we investigated the Ullmann reaction on a hexagonal boron nitride (h-BN) layer grown on an Ni(111) substrate using scanning tunneling microscopy (STM). We explored the catalytic activity of Cu and Pd atoms dosed with the molecular precursors. We found that the dispersed atoms of both metals efficiently catalyze the reaction, but lead to different reaction paths.